Deproteination and demineralization of shrimp waste using lactic acid bacteria for chitin and chitosan production - Francisco, Farramae C. (University of the Philippines Visayas, 2014)
Chitin and chitosan are valuable natural biopolymers which attention due to theri biomedical applications and can be extracted from crustacena shells through chemical and microbial processes. In this study, deproteination and demineralization efficiencies of shrimp waste using two Lactobacillus species treated with different carbohydrate sources for chitin production, its chemical conversion to chitosan and the quality of chitin and chitosan produced were determined. Using 5% glucse and 5% cassava starch as carbohydrate sources, pH slightly increased from the initial pH of 6.0 to 6.8 and 7.2, respectively after 24 h and maintained their pH at 6.7 to 7.3 throughout the treatment period. Demineralization (%) in 5% glucose and 5% cassava was highest during the first day of treatment which was 82% and 83%, respectively. Deproteination (%) was highest in 5% cassava starch on the 3rd day of treatment at 84.4%. The obtained chitin from 5% cassava and 5% glucose had a residual ash and protein below 1% and solubility of 59% and 44.3%, respectively. Chitosan pproduced from 5% cassava and 5% glucose had protein content below 0.05% ; residual ash was 1.1% and 0.8%, respectively. Chitosan solubility and degree of deacetylation were 56% and 33% in 5% glucose and 48% and 295 in 5% cassava, respectively. The advantage this alternative technology offers over that of chemical extraction is large reduction in chemicals needed thus less effluent production and generation of a protein-rich liquor, although the demineralization process should be improved ro achieve greater degree of deacetylation.